Regulation of Burkholderia cenocepacia biofilm formation by RpoN and the c-di-GMP effector BerB - Fazli, Mustafa (2018)
Knowledge about the molecular mechanisms that are involved in the regulation of biofilm formation is essential for the development of biofilm‐control measures. It is well established that the nucleotide second messenger cyclic diguanosine monophosphate (c‐di‐GMP) is a positive regulator of biofilm formation in many bacteria, but more knowledge about c‐di‐GMP effectors is needed. We provide evidence that c‐di‐GMP, the alternative sigma factor RpoN (σ54), and the enhancer‐binding protein BerB play a role in biofilm formation of Burkholderia cenocepacia by regulating the production of a biofilm‐stabilizing exopolysaccharide. Our findings suggest that BerB binds c‐di‐GMP, and activates RpoN‐dependent transcription of the berA gene coding for a c‐di‐GMP‐responsive transcriptional regulator. An increased level of the BerA protein in turn induces the production of biofilm‐stabilizing exopolysaccharide in response to high c‐di‐GMP levels. Our findings imply that the production of biofilm exopolysaccharide in B. cenocepacia is regulated through a cascade involving two consecutive transcription events that are both activated by c‐di‐GMP. This type of regulation may allow tight control of the expenditure of cellular resources.